Exploring the Concept of Debt from the Perspective of the Objectives of the Shariah - Zainol, Zairani; Nizam, Aini Nur Hajjar Khairol; Rashid, Rosemaliza Ab (International Journal of Economics and Financial Issues, 2016)
Debt is now considered a norm in everyone’s life. In Malaysia, the robust expansion of loans to the household sector has led to rising household debts. The objective of this paper is to explore the concept of debt in Islam from the perspective of the objectives of the Shariah (Maqasid Shariah) This study employs the qualitative methodology utilizing an in-depth interview with selected informants representing experts in the Shariah. The findings indicate that from the goals and objectives of the Shariah point of view, the rules for incurring debt differ according to specific circumstances. Debt should only be incurred for the purpose of necessity (daruriyyat) where the absence of debt might bring harm to the person in need. In general, acquiring debt for the purpose of complementary benefits (hajiyyat) and embellishment (tahsiniyyat) are still allowed but is not encouraged. Keywords: Debt, Islam, the objectives of the Shariah JEL Classification: H63